한반도 연안역 표층퇴적물 내 총 수은 분포 특성 - 조동진; 최만식; 김찬국; JOE, DONGJIN; CHOI, MANSIK; KIM, CHANKOOK (Pada (Hanʼguk Haeyang Hakhoe), 2018)
To determine the distribution of mercury (Hg) in the coastal surface sediments around the Korean peninsula, the baseline concentration of Hg was estimated, the extent of contamination was assessed, and the factors controlling the distribution were discussed. The concentrations of Hg in surface sediments were significantly high in Jinhae-Masan Bay in the South Sea, Ulsan-Onsan Bay and Yeongil Bay in the East Sea, but Hg in other sediments showed a similar distribution to Cs and relatively very low concentration between 0.21 and $39.5μg/kg$ ($13.6{±}7.80μg/kg$). Compared to the sediment quality guidelines in Korea, 8 % of the surface sediments (n=282) analyzed in this study exceeded the values of the threshold effects level (TEL), and six sediments collected around Onsan Port were higher than the value of the probable effects level (PEL). The contamination levels of Hg were assessed by the enrichment factors using the baseline concentration (2.06Cs+1.75) based on the residual analysis from the linear regression line for Cs, and further, factors controlling the distribution of Hg were discussed by the comparison with geochemical substances depending upon the Hg enrichment level. Hg concentrations were correlated well with Cs concentration in the range of less than 1.69 of EF implying grain size control, while in the range of 1.69 and 4.03 Hg concentrations were correlated well with Fe oxyhyroxide and organic carbon contents, which indicates Hg was enriched by superior sorption capability. On the meanwhile, samples with higher EFs (4.03 to 74.9) showed fairly positive correlations with other metals (Cu, Zn, Pb) rather than geochemical substances. For samples in Youngil Bay and Ulsan-Onsan Bay (n=30), Hg concentrations were correlated only with other metals rather than geochemical substances implying simultaneous supply of metal particles from metal refineries. But samples at Gosung, Sokcho and Uljin coast were correlated well with organic carbon even though they had high EFs. In addition, samples in Jinhae-Masan Bay with high contents of S were enriched by relatively high sulfide formation. 한반도 연안역 표층퇴적물 내 수은의 농도 분포 특성을 파악하기 위하여 수은의 배경농도를 산정하고 오염도를 평가하였으며, 분포를 조절하는 요인을 파악하였다. 표층퇴적물 내 수은 농도는 남해연안의 진해-마산만, 동해연안의 울산-온산만, 영일만에서 상당히 높게 나타났으며, 그 외 퇴적물은 Cs와 유사한 분포를 보이며 $0.21{\sim}39.5μg/kg$ ($13.6{±}7.80μg/kg$) 사이의 낮은 농도를 나타내었다. 국내 해저퇴적물 해양환경기준과 비교한 결과, 전 연안의 표층퇴적물 (n=282)의 8 %가 주의기준을 초과하였으며, 동해연안의 온산항 인근 해역 (n=6)에서 관리기준을 초과하였다. Cs에 대한 선형회귀선의 잔차분석을 통해 산정한 배경농도 (2.06Cs+1.75)를 이용하여 수은 농축도를 산정하였고, 이를 이용하여 농축 정도에 따른 조절요인을 살펴보았다. 수은 농축인자 <1.69 범위에서는 퇴적물의 입도, 1.69~4.03 범위는 Fe 산화수산화물 및 유기탄소가 좋은 관계성을 보여 주요 조절요인으로 판단되었다. 4.03~74.9 범위는 다른 금속들 (Cu, Zn, Pb)과 좋은 관계성을 보였으며, 동해연안의 고성, 속초, 울진 연안에서는 유기탄소가 주요 조절요인이었고, 영일만과 울산-온산만 (n=30)에서는 주변에 위치한 중화학 공업단지의 영향으로 금속입자의 직접적인 유입에 기인한다고 판단되었다. 또한 남해연안의 진해-마산만 시료의 경우에는 상대적으로 높은 황화물 형성과 관계하여 수은 농축이 일어나는 것으로 판단되었다.